CMOS SRAM circuit design and parametric test in nano-scaled technologies : process-aware SRAM design and test - Pavlov, Andrei (Springer, 2017)
Introduction and Motivation -- SRAM Circuit Design and Operation -- SRAM Cell Stability: Definition, Modeling and Testing -- Traditional SRAM Fault Models and Test Practices -- Techniques for Detection of SRAM Cells with Stability Faults -- Soft Errors in SRAMs: Sources, Mechanisms and Mitigation Techniques.